PROPOSED BUSINESS STRATEGY FOR MULTIDISCIPLINE CONSULTANT COMPANY (CASE STUDY OF PT X) - Melati Faeroza; Mohammad Hamsal (Eqien - Jurnal Ekonomi dan Bisnis, 2022)
PT X is one of the leading multidiscipline consulting companies in Indonesia. With the emergence of COVID-19 at the beginning of 2020, the construction industry in Indonesia was also affected by declining in the growth of construction value in Indonesia by 20.92%. Of course, this also has an impact on PT X as part of the value chain in the construction industry. At the end of 2021, Indonesia’s economy grew significantly followed by Indonesia’s construction value. However, the project number of PT X was not following the growth then PT X should find a new strategy by doing external and internal analysis to improve its business strategy. This research would discuss further about suitable business strategies by analyzing its SWOT and finding its business solution with the TOWS matrix.